2022
DOI: 10.1128/jb.00112-22
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome of Epibiont Saccharibacteria Nanosynbacter lyticus Strain TM7x During the Establishment of Symbiosis

Abstract: Nanosynbacter lyticus type strain TM7x is the first cultivated member of the Saccharibacteria and the candidate phyla radiation (CPR). It was discovered to be ultrasmall in cell size with a highly reduced genome that establishes an obligate epibiotic relationship with its host bacterium.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…low nitrogen availability) [ 42 ]. Previous studies [ 15 , 17 ] indicated that the symbiosis with XH001 allows TM7x to propagate but often presents a burden to host bacteria by inducing stress response, particularly in the stable symbiosis state. We wondered whether the formation of LDs observed through fluorescence microscopy and Raman spectroscopy was due to stress-induced host response.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…low nitrogen availability) [ 42 ]. Previous studies [ 15 , 17 ] indicated that the symbiosis with XH001 allows TM7x to propagate but often presents a burden to host bacteria by inducing stress response, particularly in the stable symbiosis state. We wondered whether the formation of LDs observed through fluorescence microscopy and Raman spectroscopy was due to stress-induced host response.…”
Section: Resultsmentioning
confidence: 99%
“…1 ). Rod-shaped host cells XH001 become irregular in the XH001/TM7x coculture, which might be related to the lower expression of chromosomal partitioning genes [ 17 ]. Laurdan quantification indicated that the cell membrane fluidity or lipid packing of host cells XH001 was drastically affected due to the association with TM7x: from highly ordered to randomly distributed ( Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, through super-resolution fluorescence imaging, the morphology of co-culture XH001/TM7x was clearly discernible with around 120-nm lateral resolution under BODIPY staining ( Figure 1 ). Rod-shaped host cells XH001 become irregular shapes in the co-culture XH001/TM7x, which might be related to the lower expression of chromosomal partitioning genes (Hendrickson et al 2022). Laurdan quantification indicated that the cell membrane fluidity or lipid packing of host cells XH001 was drastically affected due to the association with TM7x: from highly ordered to randomly distributed ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…will greatly facilitate the cultivation of CPR organisms from diverse environments for comprehensive study under well-controlled laboratory conditions. Meanwhile, high-resolution imaging techniques, such as electron microscopy and real-time live cell imaging ( 6 ), combined with bioinformatics-based metabolic network analysis ( 18 ) and multiomics studies ( 19 , 20 ) will help shed light on the intricate symbiotic relationship between CPR and their hosts. More effort should be made to develop genetic tools that can be applied to CPR for a detailed mechanistic understanding of their unique biology at the gene level ( Fig.…”
Section: High-resolution Live Cell Imaging Reveals T4p-mediated Symbi...mentioning
confidence: 99%